Helicopters - Loves, June.; Lucia, Lorenzo (Broomall, PA : Chelsea House Publishers, 2002)
Provides photographs and information about different types of helicopters, how they work, and how they have been used through history; and includes a flight time line, and a glossary.
"First published in 2000 by Macmillan Education Australia ... South Yarra, Australia"--T.p. verso.
Includes index.
Library Talk.
6.5
3-6
Keywords: Flight -- Juvenile literature; Helicopters -- Juvenile literature; Flight; Helicopters; Flight; Helicopters